SOSIALISASI ALAT PELINDUNG DIRI UNTUK MENJAGA KESELAMATAN DAN KESEHATAN KERJA KEPADA PEKERJA LAPANGAN - Didik Supriyanto (Nindikayla Institute, 2023)
Obligations regarding K3 have been agreed upon by the government through the Ministry of Manpower and Transmigration of the Republic of Indonesia. This is written in the Regulation of the Minister of Manpower and Transmigration No. Per.08 / Men / VII / 2010 concerning personal protection. Service in this case will explain the use of personal protective equipment as an effort to maintain occupational safety and health at the work site or the construction of the Perumda Tugu tirta Malang City water reservoir and provide education on how to increase workers' awareness and knowledge of the dangers / risks if Personal Protective Equipment is not used properly or not in accordance with the work being done. The objectives of this service are: 1.Knowledge of Personal Protective Equipment (PPE) as an effort to maintain occupational safety and health. 2.Management and raising awareness of Personal Protective Equipment (PPE) in the workplace and the dangers/risks if PPE is not used. The implementation methods include: Lecture Contains an explanation of Personal Protective Equipment, its functions and types and field visits Contains direct knowledge of the impact of the dangers caused by not using Personal Protective Equipment on the construction work of the Perumda Tugu tirta water reservoir in Malang City. Conclusion Participants are accustomed to using PPE and always pay attention to the PPE used that is suitable for use and in accordance with workplace conditions. It is hoped that this service will be used as a form of concern for workers who work in construction activities and reduce work accidents due to worker negligence at work.